Os DNA sintéticos anti-sentido - Cravador, A. (2012)
ANTISENSE SYNTHTETIC DNA. One old dream of the chemist in the field of the drug research is to create molecules capable of reaching their target with the precision of a missile. To accomplish it these molecules must have the propriety of distinguishing qualitative differences between healthy and diseased cells. A therapy based on this principle, able of eradicating specifically defective cells, or cells affected by a pathogen has an enormous advantage with the regard to the classical approach in which the cytotoxic drugs merely exploit quantitative biochemical and kinetic differences between abnormal and normal cells. We present in this article a review on the chemical synthesis of analogues of desoxyribonucleotides and on results obtained on the specific and irreversible inhibition of undesired genetic expression using the antisense principle.